The fallibility and future of leadership according to Jeremiah 23:1-4 - Wessels, W. J. (Old Testament essays, 1993)
The aim of this article is to view this section within its immediate context, the kingship cycle of 21:1-23:8. In it the leadership in Judah is found to be under attack forfaiting to be good shepherds. This section is descriptionbed as the culminating point of the frustration of the prophet, and no future for traditional kingship is expressed. A second aim is to look at this section (23:1-4) from a (re)constructed view of Jeremiah (the prophet presented by the book) on kingship in general. His view on kingship seems to be influenced by Northern kingdom views and principles on how a king should act. This Deuteronomic ethic seems to form the foundation of his severe criticism.